Analysis Of Fan Automatically Using Sensor Temperature - Goesty Y D; Cucus A (International Conference on Engineering and Technology Development (ICETD), 2017)
Introduction1.1BackgroundThe Internet of Things (IOT) is a network of physical objects - tools, vehicles, buildings and other items that have electronic devices, software, sensors internet and network connectivity - that allowsthese objects to collect and exchange data. Internet of Things enables objects that exist and can be controlled remotely across the network infrastructure available, creating opportunities for the directintegration of the physical world into the computer-based system and result in increased efficiency, accuracy and economic benefits. IOT is used with sensors and actuators, the technology becomes amore common use of thesystem, cyberwhich also includes technologies such as smart grids (intelligent electricity networks), smart home, smart transport and smart cities. Every thing is uniquelyidentified via an embedded computing systems (embedded) but is able to join in the Internet infrastructure.